An Experimental Study Of Di Diesel Engine Fuelled With Emulsion Fuel - Mohd Herzwan, Hamzah; Abdul Adam, Abdullah; Mohd Aminuddin, Ayob (2012)
Engine performance in term of fuel consumption and exhaust temperature of a diesel engine fuelled with emulsion fuel were observed. Emulsion fuel used in this experiment is a blend of 79% of diesel fuel, 20% of water and 1% of surfactant. This experiment compares the effect of usage between emulsion fuel and diesel fuel to single cylinder diesel engine. This experiment is conducted using a single cylinder diesel engine brand Yanmar TF 120, 4 stroke, water cooled. The engine speed is set up to 1200, 1500, 1800 and 2100 rpm and the data is taken at each engine speed. The data that is observed and collected is fuel consumption and exhaust gas temperature at each engine speed of every fuel type usage. From analysis of the experiment, it is observed that the fuel consumption due to usage of emulsion fuel is lower compared to diesel fuel after the content of the diesel fraction (79% diesel content) in the emulsion fuel is taken into account. The amount of energy consumed when emulsion fuel used (without 79% of diesel oil content is taken into account) is lower than diesel fuel by 14.7%. For the exhaust temperature, the temperature due to usage of emulsion fuel is same with diesel fuel for engine speed 1200, 1500 and 1800rpm while for 2100 rpm, the exhaust temperature when the engine is operating with emulsion fuel is lower than the diesel fuel.